2014
DOI: 10.1016/j.exppara.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and histopathological profile of Rattus norvegicus (Wistar) experimentally infected by Angiostrongylus cantonensis (Chen, 1935)

Abstract: Eosinophilic meningitis is a disease characterized by increased eosinophils in the cerebrospinal fluid (CSF), which is the most commonly caused by invasion of the central nervous system by helminths, as occurs in Angiostrongylus cantonensis infections. The rodent Rattus norvegicus is the definitive natural host and humans act as accidental hosts and can become infected by eating raw or undercooked snails or food contaminated with infective L3 larvae. Recently in Brazil there have been four cases of eosinophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…larvae recovered from A. fulica from the municipality of Aracaju were used to infect two specimens of Rattus norvegicus through an orogastric tube at a concentration of 50 L 3 larvae per rodent. Fifty days after infection, the animals were killed and necropsied to confirm the presence of adult A. cantonensis 22 . This procedure was carried out following the Ethics Commission on Animal Use of the Oswaldo Cruz Foundation (LW-47/14).…”
Section: Methodsmentioning
confidence: 99%
“…larvae recovered from A. fulica from the municipality of Aracaju were used to infect two specimens of Rattus norvegicus through an orogastric tube at a concentration of 50 L 3 larvae per rodent. Fifty days after infection, the animals were killed and necropsied to confirm the presence of adult A. cantonensis 22 . This procedure was carried out following the Ethics Commission on Animal Use of the Oswaldo Cruz Foundation (LW-47/14).…”
Section: Methodsmentioning
confidence: 99%
“…Both infection by A. cantonensis and oral exposure to the herbicide Roundup ® promoted alterations in the hepatic metabolism of R. norvegicus. Garcia et al [20] observed similar results in Wistar rats infected by A. cantonensis, possibly associated with the excretion or secretion products of the larval stages and adult helminths, which can increase the permeability of the hepatocyte membrane and consequently promote the outflow of enzymes o liver-specific cells in the blood [33][34][35] can significantly increase the serum activity of ALT and AST in Mus musculus mice and R. norvegicus Wistar rats [7,36]. This could be a consequence of an increase in the lipoperoxidation process due to the strong capacity of the herbicide to stimulate the production of reactive oxygen species [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Infection (CI) caused by A. cantonensis increased the activity of ALP in the blood of rodents, suggesting cholestasis. Garcia et al [20] proposed that infection by A. cantonensis impairs bile flow and solubilization of this enzyme in hepatocyte membranes, and consequently increases serum availability [32,37]. Furthermore, it has been postulated that liver tissue damage caused by helminth infection may result in cytolysis of hepatocytes, resulting from cell membrane damage and enzyme release into the bloodstream [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations